(untitled) (Bangladesh Journal of Agriculture, 2025)
This study investigates the genetic variation, vigor, and performance of onion generations resulting from crosses. The experiment was conducted at the Spices Research Centre, Shibganj, Bogura, during 2021-22, following diallel mating design with three parental varieties, BARI piaz1, BARI piaz4, and BARI piaz6. The research focuses on evaluating yield and yield-contributing traits, including bulb dimensions, bulbing index, and individual bulb weight. The results demonstrate significant genetic diversity among onion generations, offering opportunities for the breeders to select and develop superior lines. Hybrid vigor and heterosis, particularly evident in F1 generations, suggest that combining genetically diverse parental lines can lead to progeny with superior performance compared to their parents. However, the choice of parental lines significantly influences the stability and performance of hybrid progeny, with certain varieties demonstrating consistent performance across generations (Parent, F1, F2). Trait segregation and variability within F2 hybrid populations underscore the importance of evaluating large populations to identify individuals with desired trait combinations. Overall, the findings highlight the importance of leveraging genetic diversity and hybrid vigor in onion breeding programs to develop cultivars. By employing breeding strategies the high-performing onion varieties capable of thriving in diverse agro-climatic conditions in onion farming. Bangladesh J. Agri. 2024, 49(2): 31-44